HUBUNGAN TINGKAT PENGETAHUAN IBU YANG MEMPUNYAI BALITA TENTANG MANFAAT PENGGUNAAN POSYANDU DENGAN KUNJUNGAN IBU KE POSYANDU DI POSYANDU ARJUNA KELURAHAN SEKARAN KECAMATAN GUNUNGPATI KOTA SEMARANG - Sri Mularsih; Dewi Elliana (Jurnal Ilmiah Kesehatan, 2023)
Posyandu is a form of Community Resource Health Effort (UKBM) which is organized from, by, for and with the community in implementing health development to empower the community and make it easier for the community to obtain basic health services to accelerate the reduction in maternal and infant mortality rates. This research uses a cross-sectional design, according to the type used by this researcher, it is a correlation research type. The population in this study were mothers who had toddlers (1-5 years), namely 51 respondents, who were used as a sample of 51 respondents using total sampling techniques. The hypothesis test used in this research is chi square, to determine the relationship between two variables. The results of this research were that the majority of respondents had sufficient knowledge, 21 (41.2%) respondents. Respondents visited good posyandu (8x a year) as many as 24 (47.1) and bad ones (<8x a year) as many as 27 (52.9%). There is a relationship between the level of knowledge of mothers who have toddlers (1-5 years) about the benefits of using posyandu and the mother's visit to posyandu at Posyandu Arjuna, Sekaran Village, Gunungpati District, Semarang City. Chi Square results obtained p value (0.002 <0.05)